Association of vitamin D receptor gene TaqI polymorphism with Alzheimer's disease in a Southeastern European Caucasian population - Dimitrakis,E.; Katsarou, M. S.; Lagiou, M.; Papastefanopoulou,V.; Stanitsa,E.; Spandidos, D.A.; Tsatsakis, A.; Papageorgiou, S.; Moutsatsou, P.; Antoniou, K; Kroupis, C.; Drakoulis, N. (Exp.Ther.Med., 2022)
The role of vitamin D in Alzheimer's Disease (AD) has been studied over the past years. The results from numerous studies have indicated that the molecular pathways involved in the development of AD are closely related to the molecular pathways of the mechanisms of action of vitamin D. However, only a limited number of studies have described the key role of vitamin D receptor (VDR) in the regulation of the functions of vitamin D and the potential effect of single nucleotide polymorphisms (SNPs) of the VDR gene. Thus, the aim of the present study was to investigate the VDR TaqI polymorphism in relation to AD in a Southeastern European Caucasian (SEC) cohort. Further, the present study aimed to compare the results obtained with those of other AD populations. For this purpose, blood samples from 90 confirmed patients with AD [median age, 74 years; median mini-mental state examination (MMSE) score of 21; median frontal assessment battery (FAB) score of 10] and 103 healthy controls (median age, 57 years) were analyzed to determine the genotypes of TaqI (rs731236) using quantitative PCR. The frequencies (%) of the TaqI TT, TC and CC genotypes in the controls/patients were 34/48.9, 47.6/41.1 and 18.4/10.0, respectively. Statistically significant differences were observed for the TaqI C allele [odds ratio (OR). 0.54; 95% confidence interval (CI), 0.30-0.96; P=0.035], the TaqI TT genotype (OR, 1.86; 95% CI, 1.04-3.32; P=0.035) and the TaqI CC genotype (OR, 0.119; 95% CI, 0.014-0.995; P=0.032,) in relation to the MMSE score <21 in the patient's group. The TaqI TT allele was found to increase the risk of developing AD by 1.86-fold in the SEC population, while the TaqI C allele may act protectively, with a 46% lower risk of developing the disease. Patients with the TaqI CC genotype were found to have an 88% less likelihood of developing severe cognitive impairment based on the MMSE score. On the whole, the present study did not confirm the results of previous studies on the VDR TaqI C allele in patients with AD
IS - 1792-1015 (Electronic) IS - 1792-0981 (Print) IS - 1792-0981 (Linking) LA - eng PT - Journal Article
Keywords: Blood